The double challenge (preoperative diagnosis and surgical approach) of primary leiomyosarcoma of the sigmoid colon - Lorenzo Pagliai; Annicchiarico, Alfredo; Morini, Andrea; Montali, Filippo; Virgilio, Edoardo; Costi, Renato (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Primary colonic leiomyosarcoma (cLMS) is a rare malignancy of muscularis mucosae or muscularis propria showing highly aggressive behaviour and poor prognosis. To date, making a preoperative diagnosis and performing the most appropriate treatment represent laborious tasks for the clinicians. On the one hand, in fact, cLMS diagnosis is often difficult to achieve preoperatively because of the low specificity of clinical, radiological and bioptical features: for these motives, the diagnosis is usually obtained at postoperative histology/immune-histochemistry. On the other hand, although surgery represents the mainstay of multi-modal treatment, in the current era of minimally invasive surgery the optimal approach to cLMS is debated: in the absence of a standardized and unanimous algorithm, in fact, laparoscopy is usually proposed for small tumors, whereas laparotomy for masses exceeding 4 cm in diameter. Our aim was to elucidate such two aspects by reporting our experience.Methods: We present the case of a 51-year-old man affected with a 6-cm LMS of the sigmoid colon.Results: Preoperative diagnosis was achieved through a preoperative echo-endoscopic biopsy. The lesion was successfully and safely managed by laparoscopic surgery.Conclusions:  Our case suggests that a preoperative diagnosis of cLMS is possible in an appropriate setting. Moreover, laparoscopy seems to be a safe and successful approach to resect cancers even larger than the common 4 centimetres proposed by the current literature.